NOVEL AMPEROMETRIC SENSOR FOR THE DETECTION OF THE ANESTHETIC-GASES ISOFLURANE AND NITROUS-OXIDE - Compton, R; Northing, R (1990)
A novel gas phase sensor for the detection of the anaesthetic isoflurane is described. This consists of a channel electrode flow cell with a gas-permeable membrane located immediately upstream of a detector electrode. Substrate entering the cell is transported, in acetonitrile solution, to the electrode where it is detected via electrochemical reduction mediated through the radical anion of fluoranthene. Theory is given relating the observed detector current to the gas concentration and it is shown that the device may be extended to the detection of nitrous oxide. Advantages compared to the conventional Clark electrodes are noted. In particular it is shown that, with an additional electrode upstream of the membrane to electrogenerate an efficient oxygen scavenger, analysis of gas mixtures of isoflurane or nitrous oxide containing up to 50% oxygen is possible. A device response time of below 10 s is reported.